ANALISIS PEMBERITAAN TENTANG UNISSULA DI MEDIA CETAK (ANALISIS ISI PEMBERITAAN HARIAN SUARA MERDEKA DAN JAWA POS) - Made Dwi Adnjani; - Mubarok (Jurnal Ilmiah Komunikasi Makna, 2011)
For an educational institution, the news media is an integral part of efforts to establish a pretentious image at the position of the institution in the public eye. Sultan Agung Islamic University (UNISSULA) as universities are concerned to get a positive image of the news media. The involvement of the press in the formation of the real image of an institution involves the contestation of interest from a variety of interests. In this context, the press examined the extent of professionalism in maintaining the independence and impartial coverage of one of the colleges. Broadly speaking there are two forces that could affect the independence of the press so directly and not the attitude of the press will be impartial in reporting. The fi rst comes from the internal strength of the press itself that journalists and news managers in the form of misuse of the press for its own pragmatic interests. Both come from the external power (capital, country, culture, communalism) who uses the press to their own interests. By looking at these conditionsinteresting to observe how the attitude of the media in reporting about UNISSULA? Suara Merdeka daily electoral reasons and because Jawa Pos as national media they read the millions of people and potentially affect public attitudes. This type of research is analytical descriptive research that aims to describe and analyze a phenomenon. The method used in this research is method of quantitative content analysis. The results showed that the obtained results for Suara Merdeka CR value of 90% and 100%Jawa Pos. That amount exceeds the value requirement, is 80%. This condition indicates that the measuring instruments used reliable and meet the rule requirements. Agreement between the two koder show that the news about UNISSULA in both media is positive. News about Jawa Pos UNISSULA in media numbers are still lacking, even in February, September and October there was no news about UNISSULA in Jawa Pos. News of UNISSULA in both media are mostly news about the organization of activities and UNISSULA and be straight news. News that are analyzed and the results of in-depth reportage reporter has not been found.